Antigenic differences between Parastrongylus cantonensis and Parastrongylus malaysiensis revealed by a monoclonal antibody - Eamsobhana, Praphathip; Yong, Hoi Sen; Mak, J.W.; Wattanakulpanich, D. (Elsevier, 1997)
Objective: To confirm antigenic differences between Parastrongylus cantonensis and Parastrongylus malaysiensis.